1981
DOI: 10.1007/bf00441325
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth retardation

Abstract: Two cases of severe intrauterine growth retardation, a boy and a girl studied for 7 and 10 years respectively, are reported. Both patients showed peculiar cranio-facial abnormalities as observed in the so-called Seckel's syndrome, an appearance of premature aging, peripheral GH resistance which was probably due to deficiency in Somatomedin A production, sella areas and volumes consistently at the upper limits of normal when related to the patients' height, and dysharmonic skeletal maturation ivory cone-shaped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Majewski et al [1982b] also described the characteristic facial features and the progressive bony dysplasia. Poznanski et al [1983] clarified the radiological changes of two affected individuals who had been reported previously by Pasquino and Iannaccone [1978] and again by Boscherini et al [1981]. Willems et al [1987] reported a family with consanguinity and suggested that there might be an autosomal recessive basis for the disorder and Verloes et al [1987] reported another consanguineous family with two affected siblings.…”
Section: Historical Perspectivementioning
confidence: 49%
See 3 more Smart Citations
“…Majewski et al [1982b] also described the characteristic facial features and the progressive bony dysplasia. Poznanski et al [1983] clarified the radiological changes of two affected individuals who had been reported previously by Pasquino and Iannaccone [1978] and again by Boscherini et al [1981]. Willems et al [1987] reported a family with consanguinity and suggested that there might be an autosomal recessive basis for the disorder and Verloes et al [1987] reported another consanguineous family with two affected siblings.…”
Section: Historical Perspectivementioning
confidence: 49%
“…Similarly, non-English publications of Anoussakis et al [1974] and Pasquino and Iannaccone [1978] described individuals with very similar features of severe IUGR and severe postnatal growth restriction. Boscherini et al [1981] reported the Italian individual again, in English this time. Majewski et al [1982a] and other authors reviewed reported cases of Seckel syndrome and distinguished three specific types of primordial osteodysplastic dwarfism (e.g., primordial ¼ the features were present during early in utero development, osteodysplasia ¼ abnormalities in bony growth; and dwarfism ¼ disproportionate short stature) and distinguished them from Seckel ''bird-headed'' dwarfism [Majewski andGoecke, 1982, 1998;Majewski et al, 1982a,b;Majewski, 1992] in which more severe microcephaly was present at birth, and the IUGR was less severe, as was postnatal growth deficiency.…”
Section: Historical Perspectivementioning
confidence: 88%
See 2 more Smart Citations
“…In this review, leukocytosis and/or thrombocytosis was not mentioned as a finding . Our search of the literature showed that no study provided the leukocyte or platelet counts in patients with MOPD II , except for the above mentioned two case reports and Case 6 in the present study, which had been previously published in relation to moyamoya and recurrent strokes .…”
Section: Discussionmentioning
confidence: 60%